Answer:
A is correct
Explanation:
What we need to do here is to multiply all the roots together
The roots are;
3, √5 and -√5
Let’s have them in form of a sum
if x = 3, then the root is x-3
If x = √5, then the root is x-√5
If x = -√5, then the root is x+ √5
Now we need to multiply all these together to arrive at the original polynomial
Let’s start by using the roots
(x-√5)(x+ √5)
we can use the difference of 2 squares here and we arrive at (x^2 -5)
So finally, the polynomial would be;
(x^2-5)(x-3)
= x(x^2-5) -3(x^2-5)
= x^3-5x-3x^2+15
By rearranging, we have;
x^3-3x^2-5x+15